Targeting cystatin F activation enhances NK cell cytotoxicity in glioblastoma models - Senjor, Emanuela; Habič, Anamarija; Švajger, Urban; Mitrović, Ana; Proj, Matic; Porčnik, Andrej; Prestor, Borut; Jerala, Miha; Bošnjak, Matic; Gobec, Stanislav; Breznik, Barbara; Kos, Janko; et al. (Frontiers in Immunology, 2025)
IntroductionGlioblastoma (GBM) is a highly invasive brain tumor with limited treatment options and poor prognosis. Natural killer (NK) cells are key effectors of antitumor immunity, capable of eliminating cancer stem-like cells. However, GBM creates an immunosuppressive microenvironment that limits NK cell function. Here, we identify cystatin F as an immunosuppressive factor involved in regulating NK cell granule-mediated cytotoxicity.MethodsWe analyzed cystatin F expression in GBM and its correlation with immune exhaustion markers. NK cell activity was compared between GBM patients and healthy donors. In vitro co-cultures of cystatin F-expressing microglial cells and glioblastoma stem-like cells were used to assess NK cell function. To block cystatin F activation from dimeric to active monomeric form, a small-molecule inhibitor of cathepsin V, the activating protease, was applied.ResultsCystatin F expression correlated with immune exhaustion and suppression markers in GBM. NK cells from patients showed reduced cytotoxicity compared to healthy donors. Co-cultures confirmed that cystatin F-expressing microglia impaired NK cell cytotoxicity, while inhibition of cathepsin V restored NK cell function in standard cytotoxicity assays, 3D spheroids, and microfluidic perfused models.DiscussionThese results indicate that cystatin F mediates NK cell suppression in GBM. Targeting its activation enhances NK cell cytotoxicity, offering a potential strategy to improve NK-based immunotherapy for glioblastoma.